Information Asymmetry and Partner Selection in International Alliances - Joshi,Amol; Lahiri,Nandini (Academy of Management Proceedings, 2012)
We extend prior research on intra-firm language barriers by investigating inter-firm language barriers in cross-border alliances. Integrating concepts from sociolinguistics and information economics, we posit that language barriers between potential partners exacerbate information asymmetries, while market signals of the commercial value of a partner’s knowledge counteract these asymmetries. To test these ideas, we quantify language barriers using a distance measure of linguistic differences and we analyze data on semiconductor alliances during 1988-2001. Controlling for cultural, geographical, and technological distances, our empirical results suggest that firms overcome large language distances by relying on market signals of a prospective partner's level of disclosure, stock of knowledge, and degree of specialization. Stronger signals significantly dampen the negative impact of language distance on the chances of forming an alliance.
Keywords: Strategy & Entrepreneurship